2020
DOI: 10.6004/jnccn.2020.7541
|View full text |Cite
|
Sign up to set email alerts
|

The State of Cancer Care in America: Impact of State Policy on Access to High-Quality Cancer Care

Abstract: Health policy in America has shifted rapidly over the last decade, and states are increasingly exercising greater authority over health policy decision-making. This localization and regionalization of healthcare policy poses significant challenges for patients with cancer, providers, advocates, and policymakers. To identify the challenges and opportunities that lay ahead of stakeholders, NCCN hosted the 2019 Policy Summit: The State of Cancer Care in America on June 27, 2019, in Washington, DC. The summit feat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
1
1
0
Order By: Relevance
“…26 Our results also confirmed an advantage of immunotherapy among a cohort that included a range of payers (12% had Medicaid or were uninsured), which is important as payer status has been associated with both the delivery of care and potentially the outcomes of cancer treatment. 27,28 The majority of patients in this study (65%) were treated differently than in the PACIFIC trial, which is in line with findings in the PACIFIC-R multinational observational trial where the median time to treatment was 52 days (survival not characterized). 29 Our results suggest there may be flexibility in the time to initiate immunotherapy after the completion of radiation.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…26 Our results also confirmed an advantage of immunotherapy among a cohort that included a range of payers (12% had Medicaid or were uninsured), which is important as payer status has been associated with both the delivery of care and potentially the outcomes of cancer treatment. 27,28 The majority of patients in this study (65%) were treated differently than in the PACIFIC trial, which is in line with findings in the PACIFIC-R multinational observational trial where the median time to treatment was 52 days (survival not characterized). 29 Our results suggest there may be flexibility in the time to initiate immunotherapy after the completion of radiation.…”
Section: Discussionsupporting
confidence: 86%
“…The current study found the survival advantage of immunotherapy persists in patients 75 years or older, consistent with a subsequent post hoc analysis in the PACIFIC cohort . Our results also confirmed an advantage of immunotherapy among a cohort that included a range of payers (12% had Medicaid or were uninsured), which is important as payer status has been associated with both the delivery of care and potentially the outcomes of cancer treatment …”
Section: Discussionmentioning
confidence: 99%